Tsunami analytical fragility curves for the Colombian Pacific coast: A reinforced concrete building example. (1st October 2019) - Medina, Sergio; Lizarazo-Marriaga, Juan; Estrada, Martin; Koshimura, Shunichi; Mas, Erick; Adriano, Bruno
Highlights: Tsunami Analytical fragility curves for pre-code buildings were developed. An integrated tool has been developed to construct probabilistic fragility curves. Structural damage of buildings was accounted for the structural capacity curve. Abstract: From the last large seismic movements generated in the Pacific Ocean, it has been demonstrated that tsunamis have a high potential of destruction of buildings on the coasts. In that sense, although along the Pacific Colombian coast several earthquakes that have generated tsunami were reported during the last century, there are no local data to quantify the physical damage that future events could produce on nearby cities. For the purpose of establishing tools to increase the risk management capabilities along the Colombian-Ecuadorian Pacific Coast, this paper summarizes a research aimed to describe a new integrated methodology to obtain fragility curves for local buildings at risk of a tsunami. This task was accomplished using computational nonlinear structural analysis, combined with a Monte Carlo statistical algorithm to obtain numerical probabilistic fragility curves. The structural capacity of buildings was obtained from nonlinear structural simulations using the finite element method, to calculate later the damage of each building. Two different damage models to estimate the probability of damage were tested in order to evaluate the one that better represents the structural behavior of buildings, in which the tsunami was considered in the structural model as forces scattered to different heights, thus representing different flow depths. As a result, a methodology was developed to calculate theoretical probabilistic fragility curves for the typical structures found in the Colombian Pacific coast, although this methodology could be expanded to any structural system located in any region around the world. As an illustrative example, the methodology proposed in this research was applied to a typical reinforced concrete building, obtained from a previous work in which all the Tumaco city buildings were characterized according to their structural features.